The cult of St. Bruno of Kwerfurt in the Diocese of Ełk (1992-2022) - Guzewicz, Wojciech (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
The problem discussed in this article focuses on the cult of St. Bruno of Kwerfurt in the Diocese of Ełk in the years 1992-2022. In addition to analyzing various forms of worship, an important scientific question was resolved here: Whether St. Brunon is the patron of the diocese of Ełk? It was stated, inter alia, that although the cult of St. Bruno of Kwerfurt was and is still initiated and supported in the Ełk diocese (both by the faithful and by individual bishops and priests), for example by organizing the annual St. st. Bruno, but it has no formal legal basis. Both the papal briefs of John Paul II and the decree of the Congregation for Divine Worship and the Discipline of the Sacraments of 1993 clearly and finally defined which patrons are granted to the Ełk diocese. In both cases, there is no mention of St. Bruno from Kwerfurt. The whole argument was based on the archival and source material base.